Effect of Fly Ash as Partial Replacement of Cement in Aggressive Environment - Irwan Ridwan Rahim (International Association of Lowland Technology, 2020)
Based on the Appendix I of Peraturan Pemerintah RepublikIndonesia No. 101 year of 2014 on the management ofHazardous and Toxic waste, fly ash is categorized asHazardous and Toxic waste with a waste code B409. Fly ashcan be used as a cement replacement material in themanufacture of concrete because it contains alumina and silicawhich can be used as construction raw material. The cost ofmaking fly ash mortar is slightly more expensive thanconventional mortar. It is because of mortar fly ash useschemical activators. Several literature reviews show that fly ashbasedmortar having good mechanical character, power andgood performance in acidic and sulfate environments. In thisresearch, fly ash mortar was made using curing (treatment) thatis 24 hour and 48 hours of curing oven. In this researchsimulated on aggressive environment that is 5% of H2SO4 and10% of HCl for 0, 7, 14, and 28 days. Due to functioning as abuilding construction material, it is necessary to test the loss ofcompressive strength and weight loss. The test was performedfor 0, 7, 14 and 28 days with the result: 1) fly ash mortar hadloss of compressive strength and optimum weight loss at theage of 7 days each on the 24-hour of curing oven and 48-hourof curing oven.2) although the cost the production of fly ashmortar in general is slightly more expensive than cementmortar, but in terms of environmental aspects it has a significanteffect on CO2 reduction than the cement production using coalcombustion.